Cancer incidence among capacitor manufacturing workers exposed to polychlorinated biphenyls. Issue 2 (6th January 2017) - Ruder, Avima M.; Hein, Misty J.; Hopf, Nancy B.; Waters, Martha A.
Abstract : Background: We evaluated cancer incidence in a cohort of polychlorinated biphenyl (PCB) exposed workers. Methods: Incident cancers, identified using state registries, were compared to those in a national population using standardized incidence ratios. Trends in prostate cancer incidence with cumulative PCB exposure were evaluated using standardized rate ratios and Cox regression models. For selected sites, cumulative PCB exposure was compared between aggressive (fatal/distant stage) and localized/regional cancers. Results: We identified 3, 371 invasive first primary cancer diagnoses among 21, 317 eligible workers through 2007. Overall relative incidence was reduced. Elevations were only observed for respiratory cancers and among women, urinary organ cancers. Among men, prostate cancer incidence was reduced and not associated with cumulative PCB exposure although median exposures were significantly higher for aggressive compared to localized/regional prostate cancers. Conclusion: Previously observed associations between cumulative PCB exposure and prostate cancer mortality were not confirmed in this analysis; prostate cancer stage at diagnosis may explain the discrepancy. Am. J. Ind. Med. 60:198–207, 2017. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.